Adaptation of Pseudomonas aeruginosa biofilms to tobramycin and the quorum sensing inhibitor C-30 during experimental evolution requires multiple genotypic and phenotypic changes. Issue 1 (18th January 2023) - Bové, Mona; Kolpen, Mette; Lichtenberg, Mads; Bjarnsholt, Thomas; Coenye, Tom
Abstract : In the present study we evaluated the fitness, antimicrobial susceptibility, metabolic activity, gene expression, in vitro production of virulence factors and in vivo virulence of experimentally evolved Pseudomonas aeruginosa PAO1. These strains were previously evolved in the presence of tobramycin and the quorum sensing inhibitor furanone C-30 (C-30) and carried mutations in mexT and fusA1 . Compared to the wild-type (WT), the evolved strains show a different growth rate and different metabolic activity, suggesting they have an altered fitness. mexT mutants were less susceptible to C-30 than WT strains; they also show reduced susceptibility to chloramphenicol and ciprofloxacin, two substrates of the MexEF-OprN efflux pump. fusA1 mutants had a decreased susceptibility to aminoglycoside antibiotics, and an increased susceptibility to chloramphenicol. The decreased antimicrobial susceptibility and decreased susceptibility to C-30 was accompanied by a changed metabolic activity profile during treatment. The expression of mexE was significantly increased in mexT mutants and induced by C-30, suggesting that MexEF-OprN exports C-30 out of the bacterial cell. The in vitro production of virulence factors as well as virulence in two in vivo models of the strains evolved in the presence of C-30 was unchanged compared to the virulence of the WT. Finally, the evolved strains were less susceptible towards tobramycin (alone and combined with C-30) in an in vivo mouse model. In conclusion, this study shows that mutations acquired during experimental evolution of P. aeruginosa biofilms in the presence of tobramycin and C-30, are accompanied by an altered fitness, metabolism, mexE expression and in vitro and in vivo antimicrobial susceptibility.